Viscoelastic constitutive modeling of solid propellant with damage. (February 2016) - Yun, Kyeong-Soo; Park, Jae-Beom; Jung, Gyoo-Dong; Youn, Sung-Kie
Highlights: A new type of softening function is suggested to represent the softening phenomena which are affected by growth of void, stress state and adhesion energy in the interface. The viscoelastic dewetting function is derived from the viscoelastic dewetting criteri on to obtain the volumetric strain at the onset of the dewetting. The model is implemented into the commercial finite element code ABAQUS via the user subroutine UMAT to validate the constitutive model. Abstract: An isotropic nonlinear viscoelastic constitutive model for solid propellant is proposed. The damage due to cyclic loading and dewetting is modeled. Dewetting is a particle-binder interfacial debonding which induces softening under severe deformation. The cyclic loading effects include rapid a decrease of stress during the unloading and large amount of hysteresis known as Mullins' effect. These effects are modeled by introducing damage functions in the free energy function. The softening due to dewetting is caused by the formation and growth of voids between the matrix and the particles, and a new damage function is proposed to represent the softening behavior. It is represented as a function of the ratio of the volumetric strains before and after dewetting. The volumetric strain at the onset of dewetting is predicted by using viscoelastic dewetting function, which is derived from the viscoelastic dewetting criterion. Cyclic loading effects are accounted for by employing another damage function which is the function of the octahedral shear strain. In addition to the material nonlinearities caused by the damage, geometrical nonlinearity is also considered. The constitutive model is implemented into the commercial finite element code ABAQUS via the user material subroutine UMAT for stress analysis. Laboratory tests of uniaxial and biaxial specimens for the stress response are performed under several different loading conditions. The material parameters and damage functions are calibrated using uniaxial tests only. The effects of strain rate, temperature and loading conditions on the stress are discussed. The computational results are compared with the experiments.